Performance Evaluation of Local Organism in Wastewater Treatment - Abdulgani, Hamdani; Wati, Hessy Rahma; Fadhil, Muhammad (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Biofilters are a type of attached growth biological treatment that is considered effective among other biological treatments because of their more affordable energy operating costs, easy maintenance and operational requirements, and low environmental impact. However, there is still minimal research related to the use of local microorganisms for biological wastewater treatment. Therefore, this study aims to improve biological wastewater treatment in the cracker industry in Indramayu using local microorganisms equipped with a biofilter that utilizes natural andesite stone as a medium for microorganism growth. The best reduction in BOD anaerobically reached 79.45% and 58.91% aerobically, obtained at a flow rate of 11.11 ml/minute on the 53rd and 45th days. The increase in the BOD/COD effluent ratio from 0.22 to 0.47 during treatment indicated a decrease in biologically degradable compounds and an increase in the effectiveness of local microorganisms in reducing organic matter. Therefore, in this study, we successfully designed a biofiltration system derived from local microorganisms to effectively remove pollutants from wastewater, particularly in the cracker industry.